Education choice under uncertainty and public policy - Vincent Hogan; Ian Walker (University College Dublin, Department of Economics, 2003)
We analyse how progressive taxation and education subsidies affect schooling decisions when the returns to education are stochastic. We use the theory of real options to solve the problem of education choice in a dynamic, life-cycle consistent, stochastic model. We show that education attainment will be an increasing function of the risk associated with education. Furthermore, this result holds whether or not agents can borrow in order to pay for education and regardless of the degree of risk aversion. We also examine the link between consumption over the life-cycle and education choice to show that higher initial wealth will usually - but not always - have a positive effect on education attainment. Finally we show that progressive taxes will tend to reduce education attainment for the poor but increase it for the rich.
hdl:10197/932
Keywords: J24; C61; D81; 330; Education Choice; Dynamic Optimization; Optimal Stopping; Uncertainty; Bildungsinvestition; Bildungsertrag; Steuerprogression; Theorie